О видовой самостоятельности гирканской гаички Parus hyrcanus Sar. et Loud - Лоскот, В.М. (Вестник зоологии, 1977)
The colour and pattern of the plumage, size and proportions of the body, distribution, nesting habits, behaviour and sounds of the Hyrcanian tit known as Parus lugubris hyrcanus were studied and compared with all subspecies of P. lugubris, basing on the author's field observations and study of all available collections of P. hyrcanus, P. lugubris and related species. This study resulted in elevating Parus lugubris hyrcanus S a r. et Loud to the rank of a species: Parus hyrcanus S a r. et L o u d. (stat. n.). A new synonymy is established: P. hyrcanus S a r. et L o u d.. 1905 (=P. lugubris talischensis S t e p an y a n, 1974), syn. n. P. hyrcanus is related to P. songarus and P. montanus.